MENINGKATKAN PRESTASI BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN TGT (TEAM-GAME-TOURNAMENTS ) - Afiyah Afiyah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2016)
The purpose of this study was to determine the increase of mathematic achievement through TGT (Team-Games-Tournaments ) learning model in the fourth graders of SD The Second State Elemetary School of Pelang, Kembangbahu District Lamongan in the academic year of 2015/2016. This study used classroom action research which consisted of several cycles with each cycle there are planning, action, observation, and reflection. The result showed that the mathematics achievement of students increased by using the learning model of TGT (Team Game Tournament).